2018
DOI: 10.1371/journal.pone.0190659
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of Kenya’s national HIV viral load program: Findings and lessons learned

Abstract: ObjectivesKenya is one of the first African countries to scale up a national HIV viral load monitoring program. We sought to assess program scale up using the national database and identify areas for systems strengthening.MethodsData from January 2012 to March 2016 were extracted from Kenya’s national viral load database. Characteristics of 1,108,356 tests were assessed over time, including reason for testing, turnaround times, test results, treatment regimens, and socio-demographic information.ResultsThe numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 25 publications
(18 reference statements)
8
58
4
Order By: Relevance
“…Our follow‐up testing rate among suspected failures (83%) was similar to recent findings in Lesotho (85%) and notably higher than rates reported previously in Swaziland (70%), Malawi (30%), Mozambique (35%) or Siaya County, Kenya (35%), . Notably, less than one‐third of suspect failures had a suppressed VL at their first follow‐up test, likely corresponding to high levels of acquired first‐line drug resistance in this mature cohort where VL‐monitoring was only recently introduced, as reported in similar settings . Access to routine VL‐testing, more frequent testing and a simple algorithm seem key to reducing treatment failure rates.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our follow‐up testing rate among suspected failures (83%) was similar to recent findings in Lesotho (85%) and notably higher than rates reported previously in Swaziland (70%), Malawi (30%), Mozambique (35%) or Siaya County, Kenya (35%), . Notably, less than one‐third of suspect failures had a suppressed VL at their first follow‐up test, likely corresponding to high levels of acquired first‐line drug resistance in this mature cohort where VL‐monitoring was only recently introduced, as reported in similar settings . Access to routine VL‐testing, more frequent testing and a simple algorithm seem key to reducing treatment failure rates.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, a recent clinical trial reported higher rates of retention, VL-suppression and referral to decentralized care in patients who received POC-VL-testing [66]. Yet, our findings (and others [17,50,53,54,56]) indicate that providing access to the technology is not enough. Regular staff training, mentoring and VL "focal-points" who monitor testing protocols are recommended.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Achieving viral suppression for children in sub‐Saharan Africa is especially challenging. Studies have reported lower viral suppression rates for children and adolescents compared to adults in Kenya (57% to 66% vs. 63% to 87%) and in other low‐ and middle‐income countries (60% to 75% vs. 85%), as well as compared to children and adolescents in high‐income countries (≥ 90%) . A range of factors can influence adherence and viral suppression for children including the child's age, familial and socio‐economic environment, stigma, disclosure, and the physical and mental health status of children and caregivers .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the online VL database is a national laboratory database that serves as the primary source for all VL test results [7].…”
Section: Data Sourcesmentioning
confidence: 99%